Analyzing the Influence of Company's Business Strategy and Its Components as a Factor of Information Risk on Excess Stock Returns - Alireza Rahrovi Dastjerdi; Daryoosh Forooghi; Zahra Moradi (Journal of Asset Management and Financing)
This study investigates the impact of a company's business strategy and its underlying components as information risk factors on the excess return of firms listed on the Tehran Stock Exchange (TSE). To address this objective, two hypotheses were formulated. A sample of 236 companies listed on the TSE from 2011 to 2022 was selected and Ordinary Least Squares (OLS) regression was employed to test the hypotheses. The findings indicate that the business strategy as an information risk factor has a significant and positive impact on excess return. Moreover, six out of eight different combinations of business strategy criteria also showed a positive and significant effect on companies' excess returns. This suggested that the components of the business strategy influenced excess stock returns in a similar manner to the overall business strategy. The results implied that investors positively priced business strategy as a risk factor. This study filled a gap in the existing literature by exploring the use of a business strategy index in pricing information risk, contributing to the finance research domain.Keywords: Business Strategy, Pricing, Information Risk, Excess Stock Returns. IntroductionIn the dynamic capital market environment, understanding the various risk factors that influence investment returns is crucial for investors and stakeholders. One such prominent factor is information risk, which pertains to the uncertainty arising from the quality, accuracy, and comprehensiveness of information available to investors. This uncertainty can significantly impact decision-making processes and market performance. This studey focused on analyzing the influence of a company's business strategy and its underlying components as factors of information risk on excess stock returns. By examining companies listed on the Tehran Stock Exchange (TSE), this study aimed to elucidate how investors perceived business strategies and how these perceptions were reflected in stock market performance. Through this lens, the study sought to contribute to the broader financial literature by integrating the concept of business strategy into the framework of information risk pricing. Exploring the relationship between business strategy, information risk, and excess returns is crucial as it can provide valuable insights for investors, stakeholders, and financial decision-makers. Understanding how the various elements of a company's business strategy are priced by the market can help investors make more informed decisions and enhance their overall investment strategies. Materials & MethodsTo address the research objectives, two hypotheses were formulated to investigate the relationship between a company's business strategy and its excess stock returns, considering information risk as a key factor. The sample comprised 236 companies listed on the TSE over the period from 2011 to 2022. The study employed the Ordinary Least Squares (OLS) regression technique to analyze the data and test the hypotheses. The business strategy was quantified using a comprehensive index that incorporated various strategic components, enabling a nuanced examination of its impact on stock returns. This approach allowed for a detailed analysis of how the different elements of a company's business strategy were perceived and priced by investors in the market. The methodology involved rigorous statistical analysis to ensure the reliability and validity of the findings, providing a robust basis for drawing meaningful conclusions. The analytical process adhered to established econometric principles and best practices, ensuring the integrity and credibility of the research. By adopting this comprehensive and rigorous approach, the study aimed to contribute to the existing financial literature by elucidating the role of business strategy as an information risk factor and its influence on excess stock returns in the context of the TSE. FindingsThe empirical analysis revealed that a company's business strategy significantly and positively influenced its excess stock returns, confirming the research hypotheses. Specifically, the overall business strategy emerged as a positive and significant factor in determining excess returns. Further examination of the individual components of the business strategy index showed that six out of eight combinations had a similarly positive and significant effect on excess returns. These findings indicated that not only did the holistic business strategy impact investor perceptions and stock performance, but specific strategic elements also played a crucial role in this relationship. The results suggested that investors appeared to price the business strategy favorably, reflecting its perceived value in the context of information risk. Investors seemed to view a company's business strategy as a vital factor in assessing the quality, accuracy, and comprehensiveness of the available information and consequently determining the appropriate risk-adjusted returns. These findings contribute to the existing financial literature by providing empirical evidence on the role of business strategy as an information risk factor and its impact on excess stock returns. The nuanced understanding of how specific strategic components influence investor perceptions and market performance can offer valuable insights for corporate decision-makers, investors, and financial analysts. Discussion and ConclusionThe study's findings highlighted the critical role of business strategy in the context of information risk and stock market performance. The positive relationship between business strategy and excess stock returns suggested that investors valued strategic clarity and transparency, which could help reduce information asymmetry and associated risks. By decomposing the business strategy into its constituent elements, the study provided granular insights, into which specific aspects of strategy were most influential in determining excess returns. These results had significant implications for both corporate management and investors. For corporate managers, the findings underscored the importance of strategic planning and effective communication in enhancing investor confidence and market performance. By aligning their business strategies with investor expectations and ensuring transparent disclosure of strategic information, companies could positively influence their excess stock returns. From an investor's perspective, understanding the strategic direction of a company could serve as a crucial tool for making informed investment decisions. By incorporating an assessment of a firm's business strategy into its risk-return analysis, investors could potentially gain a more comprehensive understanding of the information risk inherent in their investment decisions. Overall, this study contributed to the financial literature by integrating the concept of business strategy into the analysis of information risk, offering a novel perspective on its impact on excess stock returns. The findings suggested that investors positively price business strategy as a risk factor, reflecting its perceived value in the context of information risk. Future research could further explore this relationship across different markets and economic conditions to generalize the findings and enhance their applicability. Extending the analysis to other geographical contexts and time periods could provide valuable insights into the generalizability and robustness of the observed patterns.